Remote stereocontrolled asymmetric 1, 6-addition/1, 4-addition cascade reactions between cyclic dienones and 2-indolinethiones. Issue 108 (10th November 2016) - Sun, Xiaohua; Fei, Jie; Zou, Chuncheng; Lu, Min; Ye, Jinxing
Abstract : Enantioselective 1, 6-addition/1, 4-addition cascade reactions between cyclic dienones and 2-indolnethiones have been realized, affording chiral spiro[thiopyranoindole-cyclohexanone] scaffolds facilely and efficiently. Abstract : Highly enantioselective 1, 6-addition/1, 4-addition cascade reactions between cyclic dienones and 2-indolnethiones have been realized by employing a cinchona-based primary amine catalyst. This method displays a broad substrate scope and provides a simple and highly effective way to achieve the chiral spiro[thiopyranoindole-cyclohexanone] scaffold.